ANALISIS PERENCANAAN PENGEMBANGAN OBJEK WISATA KAMPUNG KELEMBAK BERBASIS MASYARAKAT, NONGSA, BATAM - I Nyoman Budhiarta; Rezki Alhamdi (UHN IGB Sugriwa Denpasar, 2023)
Kampung Kelembak Tourism Object is a tourist attraction located in Nongsa, Batam, Riau Islands. However, this tourist attraction requires more optimal development for the future in terms of its facilities to support the comfort of tourists visiting the tourist attraction. Therefore, an in-depth analysis and research is needed to find out the needs of the Kampung kelembak tourism object in terms of supporting facilities and planning and concepts that can be applied in the future. The method used in this research is qualitative in descriptive form. The informants used in this study were tourists who had traveled to the Kampung Kelembak Tourism object. The results of the study found that this kampung kelembak tourist taxi was in need of future development in terms of empowering the community, namely involving the community in every management decision, providing space for the community to meet the needs of tourists during the trip such as eating and drinking, activities at tourist objects. in the promotion section, tourism objects can invite tours and travel to make tour packages and also schools or campuses to do learning in Kampung kelembak. In the tourist attraction facilities section, directions are given to get to the interesting places provided.